(untitled) (Research, Society and Development, 2026)
The present study aimed to evaluate and compare the hematimetric profile, including hemoglobin, ferritin, and serum iron, of patients with AUB before and after treatment with levonorgestrel IUD or Combined Oral Contraceptives (COC) in a referral hospital in the North Region of Brazil. This is an observational, analytical, retrospective cohort study analyzing a sample of 30 patients, 14 in the IUD group and 16 in the COC group, evaluated at baseline (T0) and after three months of treatment (T1). The statistical analysis employed several tests with a significance level of 5%. The results showed that, at baseline, the IUD group had a more unfavorable profile. In the intragroup evaluation, the use of the levonorgestrel IUD promoted a significant increase in mean hemoglobin. The COC group stood out for the significant increase in mean serum iron, achieving a total absence of serum iron deficiency in the post-treatment period. In the comparison between the groups at T1, there was no statistical difference for hemoglobin or ferritin, but the COC group had significantly higher final serum iron levels. It can be concluded that both methods are effective in restoring hematimetric parameters in the short term, with the Mirena IUD demonstrating high efficacy in restoring hemoglobin even in more severe baseline cases, while COCs favored a more homogeneous normalization of serum iron, meaning that the choice of treatment should be individualized.